2000
DOI: 10.1542/peds.106.6.1460
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Testing of Children for Two X-Linked Diseases: A Retrospective Study of Comprehension of the Test Results and Social and Psychological Significance of the Testing

Abstract: Carrier testing was in most cases correctly understood and the matter openly discussed. Our results do not suggest that testing in childhood had caused serious harm to the young individuals tested. On the other hand, we found no obvious benefits from this early testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…These studies reported that a further 13% 40 and 4% 37 of children described positive influences on their lives. Meulenkamp et al 41 reported that 15% of children in their study reported worrying about their hereditary predisposition to cardiovascular disease, whereas 90% of children at risk for hereditary risk of acute intermittent porphyria reported that knowledge of their personal risk status had no effect on their educational, occupational, or social lives.…”
Section: Quality Of Life and Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…These studies reported that a further 13% 40 and 4% 37 of children described positive influences on their lives. Meulenkamp et al 41 reported that 15% of children in their study reported worrying about their hereditary predisposition to cardiovascular disease, whereas 90% of children at risk for hereditary risk of acute intermittent porphyria reported that knowledge of their personal risk status had no effect on their educational, occupational, or social lives.…”
Section: Quality Of Life and Behaviormentioning
confidence: 99%
“…Two studies reported that 78% of children tested for two X-linked diseases 40 and 84% of children tested for Aspartylglucosaminuria risk 37 perceived that genetic testing had no impact on their quality of life. These studies reported that a further 13% 40 and 4% 37 of children described positive influences on their lives.…”
Section: Quality Of Life and Behaviormentioning
confidence: 99%
See 3 more Smart Citations